POTENSI JAMUR ASAL UMBI TANAMAN TERNA TAHUNAN SEBAGAI PENGENDALI Ganoderma boninense PENYEBAB PENYAKIT BUSUK PANGKAL BATANG PADA KELAPA SAWIT - Muthia Amalia Cendrawati; Suwandi Suwandi; Siti Herlinda; Suparman Suparman (Jurnal Biotek, 2020)
The oil palm plantation sector is one of the largest foreign exchange earners in Indonesia. The attack of red root fungus by Ganoderma boninense causes stem rot disease (BPB) in oil palms, causing potential losses. Until now, this disease has not been controlled. Therefore, research is needed for controlling BPB disease in oil palm. This study aims to determine the ability of the biological agents explored and isolated from three types of annual herbaceous tubers, namely garut (Maranta arundinacea), ganyong (Canna indica), and talas Belitung (Xanthosoma sagittifolium)  in controlling G. boninense. A total of 24 isolates, 11 isolates from garut tubers, 9 isolates from ganyong tubers, and 4 isolates from Belitung tubers were tested for the antagonism in dual culture on Malt Extract Agar (MEA) media. The results showed that the isolates from Belitung tubers had higher antagonism than garut and ganyong. Three isolates that showed the highest antagonistic activity were TLRF3, Gytf5, and TLTF8, all of which were from the genus Trichoderma. Endophytic fungi tested have the potential to be biological agents to control BPB (Rot Pangkal Batang) disease in oil palm.